2011
DOI: 10.1097/ncc.0b013e3181f795e7
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment Decisions of Cancer Patients in Rural Western Australia

Abstract: Rural patients need help and support throughout their cancer journey, including through the process of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
18
0
3
Order By: Relevance
“…Moreover, emotional and psychosocial well-being was often maintained even when relocation was required. Factors that contributed to a greater sense of well-being while away from home included staying in affordable and comfortable accommodations, developing close ties with individuals in similar circumstances, fostering a sense of comfort by being close to expert oncology services, alleviating the demands of driving every day, or spending additional quality time with significant other (Fitch et al, 2003;Martin-McDonald et al, 2003;McConigley et al, 2011;Pesut et al, 2010).…”
Section: Social Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, emotional and psychosocial well-being was often maintained even when relocation was required. Factors that contributed to a greater sense of well-being while away from home included staying in affordable and comfortable accommodations, developing close ties with individuals in similar circumstances, fostering a sense of comfort by being close to expert oncology services, alleviating the demands of driving every day, or spending additional quality time with significant other (Fitch et al, 2003;Martin-McDonald et al, 2003;McConigley et al, 2011;Pesut et al, 2010).…”
Section: Social Domainmentioning
confidence: 99%
“…The most noteworthy finding in the reviewed studies was that participants face challenges related to service provision in their rural communities. Of the 23 studies reviewed, 10 articles revealed service provision challenges such as lack of access to cancer information, limited access to professional or hospital assistance, and isolation from professional support or other supportive services were enduring challenges (Clavarino et al, 2002;Duggleby et al, 2010;Engleman, Perpich, Peterson, Hall, & Ellerbeck, 2005;Fitch et al, 2003;Gray, James, Manthorne, Gould, & Fitch, 2004;McConigley et al, 2011;McGrath, 2001;Rogers-Clark, 2002;Wilkes, White, & Riordan, 2000;Wilkes, White, Mohan, & Beale, 2006).…”
Section: Continued On Page 161…mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the differential in health outcomes is well recognised, there is a need to understand any differences in the health services that are available to people and their caregivers, especially at the end of life. Despite the disparities that have been described, semi-structured interviews in Western Australia amongst a range of rural patients identified an overarching theme of 'implicit faith' in the health system, despite known delays and inconveniences (1). The contribution of families and friends in providing care and social support is also a critical component in rural health (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…La conclusion la plus notable parmi les études recensées était le fait que les participants connaissent des difficultés afférentes à l'offre de services dans leurs collectivités rurales. Parmi les 23 articles recensés, 10 mentionnaient des enjeux continus sur le plan de l'offre de services : manque d'accès à l'information sur le cancer, accès limité à l'assistance professionnelle ou hospitalière et éloignement de tout soutien professionnel ou d'autres services de soutien (Clavarino et al, 2002;Duggleby et al, 2010;Engleman, Perpich, Peterson, Hall & Ellerbeck, 2005;Fitch et al, 2003;Gray, James, Manthorne, Gould & Fitch, 2004;McConigley et al, 2011;McGrath, 2001;Rogers-Clark, 2002;Wilkes, White & Riordan, 2000;Wilkes, White, Mohan & Beale, 2006).…”
Section: Résultats De La Recension De La Documentationunclassified